(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This article examines recent scientific studies on Chinese-Uzbek cross-linguistics, focusing on studies of euphemism and lacuna phenomena in both languages. Modern Chinese and Uzbek linguistics focus on the study of the language, particularly the lexicon, from a semantic, linguistic, and cultural perspective. The origins of household euphemisms in Chinese and Uzbek languages and the conceptual framework in which euphemisms are manifested were determined, and through the linguistic and cultural study of household euphemisms, conclusions were drawn about the distinctive and similar aspects of the worldviews of the two peoples. Identification, classification, and systematization of lacuna varieties were also addressed. The gaps in the Chinese and Uzbek languages are categorized thematically and analyzed. The methods for filling in and eradicating translation gaps are determined.